The impact of the financial crisis on families in Spain: The case of Ourense, Spain - Verde Diego, Carmen; Prado Conde, Santiago; Aguiar Fernández, Francisco Xabier (International Social Work, 2018)
This article presents the characteristics of the impact of the financial cutbacks implemented by the Spanish neoliberal government after he onset of the 2008 financial crisis on families. In this context, the results are obtained from 22 interviews and 35 questionnaires submitted to all social workers in the province’s community social services. These results corroborate that cutbacks have had a high impact on families, both for individual family members and for the family typology itself.
Keywords: austerity policies; crisis in Spain; family typology modification; impact on family members; sandwich family; Scopus; JCR